Analisis Pengaruh Pertumbuhan Ekonomi, Tingkat Pendidikan dan Kesehatan Terhadap Jumlah Penduduk Miskin di Bali Tahun 2011-2020 - Enia Helga Pratiwi; Nazaruddin Malik (Jurnal Ilmu Ekonomi, 2022)
This study aims to determine the effect of economic growth, level of education and health on the number of poor people in the Regency/City of Bali Province. In this study, the high poverty rate in the Regency/City of the Province of Bali is a problem that will be studied. The method used in this study is a quantitative panel data method with the help of software eviews 9. The data used is secondary data, using panel data methods (cross-section) and (time series). The period in this analysis is 2007-2016 and 9 districts/cities in the province of Bali. The results showed that simultaneously the variable economic growth (X1) had a positive and significant effect on the number of poor people in the Regency/City of Bali Province. Meanwhile, the education level variable (X2) and the health variable (X3) have a negative and significant effect on the number of poor people in the Regency/City of Bali Province. This study aims to determine the effect of economic growth, level of education and health on the number of poor people in the Regency/City of Bali Province. In this study, the high poverty rate in the Regency/City of the Province of Bali is a problem that will be studied. The method used in this study is a quantitative panel data method with the help of software eviews 9. The data used is secondary data, using panel data methods (cross-section) and (time series). The period in this analysis is 2007-2016 and 9 districts/cities in the province of Bali. The results showed that simultaneously the variable economic growth (X1) had a positive and significant effect on the number of poor people in the Regency/City of Bali Province. Meanwhile, the education level variable (X2) and the health variable (X3) have a negative and significant effect on the number of poor people in the Regency/City of Bali Province.